RhoA/ROCK2 signalling is enhanced by PDGF‐AA in fibro‐adipogenic progenitor cells: implications for Duchenne muscular dystrophy. Issue 2 (7th February 2022) - Fernández‐Simón, Esther; Suárez‐Calvet, Xavier; Carrasco‐Rozas, Ana; Piñol‐Jurado, Patricia; López‐Fernández, Susana; Pons, Gemma; Bech Serra, Joan Josep; de la Torre, Carolina; de Luna, Noemí; Gallardo, Eduard; Díaz‐Manera, Jordi
Abstract: Background: The lack of dystrophin expression in Duchenne muscular dystrophy (DMD) induces muscle fibre and replacement by fibro‐adipose tissue. Although the role of some growth factors in the process of fibrogenesis has been studied, pathways activated by PDGF‐AA have not been described so far. Our aim was to study the molecular role of PDGF‐AA in the fibrotic process of DMD. Methods: Skeletal muscle fibro‐adipogenic progenitor cells (FAPs) from three DMD treated with PDGF‐AA at 50 ng/mL were analysed by quantitative mass spectrometry‐based proteomics. Western‐blot, immunofluorescence, and G‐LISA were used to confirm the mass spectrometry results. We evaluated the effects of PDGF‐AA on the activation of RhoA pathway using two inhibitors, C3‐exoenzyme and fasudil. Cell proliferation and migration were determined by BrdU and migration assay. Actin reorganization and collagen synthesis were measured by phalloidin staining and Sircol assay, respectively. In an in vivo proof of concept study, we treated dba/2J‐mdx mice with fasudil for 6 weeks. Muscle strength was assessed with the grip strength. Immunofluorescence and flow cytometry analyses were used to study fibrotic and inflammatory markers in muscle tissue. Results: Mass spectrometry revealed that RhoA pathway proteins were up‐regulated in treated compared with non‐treated DMD FAPs ( n = 3, mean age = 8 ± 1.15 years old). Validation of proteomic data showed that Arhgef2 expression was significantly increased in DMD muscles compared with healthy controls by a 7.7‐fold increase ( n = 2, mean age = 8 ± 1.14 years old). In vitro studies showed that RhoA/ROCK2 pathway was significantly activated by PDGF‐AA ( n = 3, 1.88‐fold increase, P < 0.01) and both C3‐exoenzyme and fasudil blocked that activation ( n = 3, P < 0.05 and P < 0.001, respectively). The activation of RhoA pathway by PDGF‐AA promoted a significant increase in proliferation and migration of FAPs ( n = 3, P < 0.001), while C3‐exoenzyme and fasudil inhibited FAPs proliferation at 72 h and migration at 48 and 72 h ( n = 3, P < 0.001). In vivo studies showed that fasudil improved muscle function ( n = 5 non‐treated dba/2J‐mdx and n = 6 treated dba/2J‐mdx, 1.76‐fold increase, P < 0.013), and histological studies demonstrated a 23% reduction of collagen‐I expression area ( n = 5 non‐treated dba/2J‐mdx and n = 6 treated dba/2J‐mdx, P < 0.01). Conclusions: Our results suggest that PDGF‐AA promotes the activation of RhoA pathway in FAPs from DMD patients. This pathway could be involved in FAPs activation promoting its proliferation, migration, and actin reorganization, which represents the beginning of the fibrotic process. The inhibition of RhoA pathway could be considered as a potential therapeutic target for muscle fibrosis in patients with muscular dystrophies.